2019
DOI: 10.1016/j.arth.2019.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Greater Rates of Acute Kidney Injury in African American Total Knee Arthroplasty Patients

Abstract: Background: This retrospective study compared the change in serum creatinine between African American and Caucasian Total Knee Arthroplasty (TKA) patients. The authors hypothesized that African Americans would demonstrate significantly greater change, and that a significantly greater proportion would demonstrate creatinine changes consistent with acute kidney injury (AKI). Methods: Primary TKAs performed at a single institution between July, 2011-June, 2016 were identified: 1035 primary TKAs met inclusion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Perioperative and postoperative risk factors include general anesthesia, hypovolemia, hypotension, and use of nephrotoxic medications. 16,17 CKD is a possible sequela of AKI, which can lead to hospitalization and increased mortality. 15,18 NSAIDs have a proven role in improving postoperative pain control and decreasing the opioid burden after primary total hip and total knee arthroplasties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perioperative and postoperative risk factors include general anesthesia, hypovolemia, hypotension, and use of nephrotoxic medications. 16,17 CKD is a possible sequela of AKI, which can lead to hospitalization and increased mortality. 15,18 NSAIDs have a proven role in improving postoperative pain control and decreasing the opioid burden after primary total hip and total knee arthroplasties.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative and postoperative risk factors include general anesthesia, hypovolemia, hypotension, and use of nephrotoxic medications. 16,17 CKD is a possible sequela of AKI, which can lead to hospitalization and increased mortality. 15,18…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other studies have reported significantly higher incidence of AKI along racial lines among specialized populations, including patients with diabetes [ 17 ], trauma [ 20 ], and those undergoing procedures such as percutaneous coronary intervention [ 8 , 21 ] and knee surgery [ 19 ].…”
Section: Racial Disparities In the Incidence Of Akimentioning
confidence: 90%
“…Previous studies have reported that Black patients have a disproportionately higher risk of AKI when compared with White patients [ 4 , 8 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Using self-reported Black and White participants from the Atherosclerosis Risk in Communities (ARIC) study, Grams et al [ 4 ] investigated the impact of race on the incidence of AKI-related hospitalizations.…”
Section: Racial Disparities In the Incidence Of Akimentioning
confidence: 99%
“…However, due to variations in study populations and sample sizes, different studies have identified conflicting risk factors. Several studies have shown that specific races (e.g., African-Americans) have a higher risk for VA-AKI ( Bosso et al, 2011 ; Womble et al, 2019 ); although, studies specifically investigating Asian populations are lacking. For patients developed VA-AKI, how to reduce mortality and improve renal recovery is still a difficult problem to be explored.…”
Section: Introductionmentioning
confidence: 99%